“What’s the Big Idea?” A Case Study of Whole-School Project-Based Instruction in Secondary Education - Howard, Patrick; Ryan, Chris; Fogarty, Ian (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2020)
This paper presents the results of an inquiry into a creative, whole-school integrative learning project that started with posing a ‘big question’. Data were generated to deepen understanding regarding the effects of implementing creative project-based learning Hi on student lived experience and student attitudes toward learning. Research on project-based approaches is required to reflect the current contextual realities specific to high schools. The focus on integrative and arts-based approaches as they relate to high school classrooms indicate that secondary education lags in comparison to elementary and middle grades. The findings presented here provide the possibility of a more informed, attentive, action-sensitive professional practice in the development of educational experiences designed to influence the learning experiences of secondary students.